Summation Or Something Else

Algebra Level 3

( 1 4 + 1 4 ) ( 3 4 + 1 4 ) ( 5 4 + 1 4 ) ( ( 2 n 1 ) 4 + 1 4 ) ( 2 4 + 1 4 ) ( 4 4 + 1 4 ) ( 6 4 + 1 4 ) ( ( 2 n ) 4 + 1 4 ) = 1 a n 2 + b n + c \frac {\left(1^4+\frac 14\right)\left(3^4+\frac 14\right)\left(5^4+\frac 14\right)\cdots\left((2n-1)^4+\frac 14\right)}{\left(2^4+\frac 14\right)\left(4^4+\frac 14\right)\left(6^4+\frac 14\right)\cdots\left((2n)^4+\frac 14\right)} = \frac 1{an^2+bn+c}

The equation above holds true for integers a a , b b and c c . Find a + b + c a+b+c .


The answer is 13.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Mar 20, 2018

Relevant wiki: Sophie Germain Identity

Q = k = 1 n ( ( 2 k 1 ) 4 + 1 4 ) k = 1 n ( ( 2 k ) 4 + 1 4 ) Multiply up and down by 4 n = k = 1 n ( 4 ( 2 k 1 ) 4 + 1 ) k = 1 n ( 4 ( 2 k ) 4 + 1 ) By Sophie Germain’s identity: = k = 1 n ( 8 k 2 4 k + 1 ) ( 8 k 2 12 k + 5 ) k = 1 n ( 8 k 2 + 4 k + 1 ) ( 8 k 2 4 k + 1 ) a 4 + 4 b 4 = ( a 2 + 2 a b + 2 b 2 ) ( a 2 2 a b + 2 b 2 ) = k = 1 n ( 8 k 2 12 k + 5 ) k = 1 n ( 8 k 2 + 4 k + 1 ) = ( 8 ( 1 2 ) 12 ( 1 ) + 5 ) k = 1 k = 2 n ( 8 k 2 12 k + 5 ) k = 1 n ( 8 k 2 + 4 k + 1 ) = ( 1 ) k = 1 n 1 ( 8 ( k + 1 ) 2 12 ( k + 1 ) + 5 ) k = 1 n ( 8 k 2 + 4 k + 1 ) = k = 1 n 1 ( 8 k 2 + 4 k + 1 ) k = 1 n ( 8 k 2 + 4 k + 1 ) = 1 8 n 2 + 4 n + 1 \begin{aligned} Q & = \frac {\prod_{k=1}^n \left((2k-1)^4+\frac 14\right)}{\prod_{k=1}^n \left((2k)^4+\frac 14\right)} & \small \color{#3D99F6} \text{Multiply up and down by }4^n \\ & = \frac {\prod_{k=1}^n \left(4(2k-1)^4+1\right)}{\prod_{k=1}^n \left(4(2k)^4+1\right)} & \small \color{#3D99F6} \text{By Sophie Germain's identity: } \\ & = \frac {\prod_{k=1}^n \cancel{\left(8k^2-4k+1\right)}\left(8k^2-12k+5\right)}{\prod_{k=1}^n \left(8k^2+4k+1\right)\cancel{\left(8k^2-4k+1\right)}} & \small \color{#3D99F6} a^4+4b^4 = (a^2+2ab+ 2b^2)(a^2-2ab+2b^2) \\ & = \frac {\prod_{k=1}^n \left(8k^2-12k+5\right)}{\prod_{k=1}^n \left(8k^2+4k+1\right)} \\ & = \frac {\overbrace{(8(1^2)-12(1)+5)}^{\color{#3D99F6}k=1} \prod_{\color{#3D99F6}k=2}^{\color{#3D99F6}n} \left(8{\color{#3D99F6}k^2}-12{\color{#3D99F6}k}+5\right)}{\prod_{k=1}^n \left(8k^2+4k+1\right)} \\ & = \frac {{\color{#3D99F6}(1)}\prod_{\color{#D61F06}k=1}^{\color{#D61F06}n-1} \left(8{\color{#D61F06}(k+1)^2}-12{\color{#D61F06}(k+1)}+5\right)}{\prod_{k=1}^n \left(8k^2+4k+1\right)} \\ & = \frac {\prod_{k=1}^{n-1} \left(8k^2+4k+1\right)}{\prod_{k=1}^n \left(8k^2+4k+1\right)} \\ & = \frac 1{8n^2+4n+1} \end{aligned}

Therefore, a + b + c = 8 + 4 + 1 = 13 a+b+c = 8+4+1=\boxed{13} .

Naren Bhandari
Mar 18, 2018

P = n = 1 m ( ( 2 n 1 ) 4 + 1 4 ( 2 n ) 4 + 1 4 ) P = n = 1 m ( 4 ( 2 n 1 ) 4 + 1 4 ( 2 n ) 4 + 1 ) P = n = 1 m ( 4 q 4 + p 4 4 b 4 + a 4 ) \begin{aligned} & P =\displaystyle\prod_{n=1}^{m}\left( \dfrac{(2n-1)^4+\frac{1}{4}}{(2n)^4 +\frac{1}{4}}\right) \\& P = \displaystyle\prod_{n=1}^{m} \left(\dfrac{4(2n-1)^4 +1}{4(2n)^4 +1}\right)\\& P = \displaystyle\prod_{n=1}^{m} \left(\dfrac{4q^4 +p^4}{4b^4 +a^4}\right)\end{aligned} where a = 1 , b = 2 n , p = 1 , q = 2 n 1 a =1 , b = 2n, p = 1, q = 2n-1 and using Sophie German Identity for the expansion of p 4 + 4 q 4 a 4 + 4 b 4 = ( ( p + q ) 2 + q 2 ) ( ( p q ) 2 + q 2 ) ( ( a + b ) 2 + b 2 ) ( ( a b ) 2 + b 2 ) ) p 4 + 4 q 4 a 4 + 4 b 4 = ( ( 1 + 2 n 1 ) 2 + ( 2 n 1 ) 2 ) ( ( 1 ( 2 n 1 ) ) 2 + ( 2 n 1 ) 2 ) ( ( 1 + 2 n ) 2 + ( 2 n ) 2 ) ( ( 1 2 n ) 2 + ( 2 n ) 2 ) p 4 + 4 q 4 a 4 + 4 b 4 = ( 2 n ) 2 + ( 2 n 1 ) 2 ) ( ( 2 2 n ) 2 + ( 2 n 1 ) 2 ) ( 1 + 2 n ) 2 + ( 2 n ) 2 ) ( ( 1 2 n ) 2 + ( 2 n ) 2 ) p 4 + 4 q 4 a 4 + 4 b 4 = ( 2 2 n ) 2 + ( 2 n 1 ) 2 ( 2 n + 1 ) 2 + ( 2 n ) 2 = 4 8 n + 4 n 2 + 4 n 2 4 n + 1 4 n 2 + 4 n + 1 + 4 n 2 = 8 n 2 12 n + 5 8 n 2 + 4 n + 1 \begin{aligned} & \dfrac{p^4 +4q^4}{a^4 +4b^4 } = \dfrac{((p+q)^2+q^2)((p-q)^2+q^2)}{((a+b)^2+b^2)((a-b)^2+b^2))}\\& \dfrac{p^4+4q^4}{a^4+4b^4} =\dfrac{((1+2n-1)^2 +(2n-1)^2)((1-(2n-1))^2+(2n-1)^2)}{((1+2n)^2+(2n)^2)((1-2n)^2+(2n)^2)} \\& \dfrac{p^4+4q^4}{a^4+4b^4} = \dfrac{(2n)^2 +(2n-1)^2)((2-2n)^2 + (2n-1)^2)}{(1+2n)^2+(2n)^2)((1-2n)^2 + (2n)^2)} \\& \dfrac{p^4+4q^4}{a^4+4b^4} = \dfrac{(2-2n)^2+(2n-1)^2}{(2n+1)^2 +(2n)^2} =\dfrac{4-8n +4n^2 +4n^2 -4n+1}{4n^2+4n+1 +4n^2} =\dfrac{8n^2 -12n +5}{8n^2 + 4n+1} \end{aligned} n = 1 m ( 2 n 1 ) 4 + 1 ( 2 n ) 4 + 1 = n = 1 m 8 n 2 12 n + 4 8 n 2 + 4 n + 1 = 1 8 m 2 + 4 m + 1 \therefore \displaystyle\prod_{n=1}^{m} \dfrac{(2n-1)^4 +1}{(2n)^4+1} = \displaystyle\prod_{n=1}^{m} \dfrac{8n^2-12n+4}{8n^2 +4n+1} = \dfrac{1}{\boxed{8m^2+4m+1}} Note n = 1 m 8 n 2 12 n + 5 8 n 2 + 4 n + 1 = 1 13 × 13 41 × 41 85 × × 8 m 2 12 m + 5 × 8 m 2 12 m + 5 8 m 2 + 4 m + 1 \displaystyle\prod_{n=1}^{m} \dfrac{8n^2-12n+5}{8n^2+4n+1} = \dfrac{1}{13}\times \dfrac{13}{41} \times \dfrac{41}{85}\times \cdots \times\dfrac{}{8m^2-12m+5}\times \dfrac{8m^2-12m+5}{8m^2+4m+1} shows that the above product is telescoping product.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...